Preparation of Composite Films Based on Methyl Cellulose/Polyvinyl Alcohol-loaded Nanosilver (AgNPs@PVA/MC) and Its Effect on Storage Quality of Ougan - Shuaishuai DAI; Weijie WU; Xiangjun FANG; Hangjun CHEN; Jun HUANG; Ruiling LIU; Huizhi CHEN; Ben NIU; Haiyan GAO (Shipin gongye ke-ji)
The antibacterial AgNPs@PVA/MC composite films were prepared by using methyl cellulose (MC) and polyvinyl alcohol (PVA) as composite substrate, nanosilver (AgNPs) as antibacterial agent, and glycerin as plasticizer. The effects of different mass fractions (0%, 0.05%, 0.1%, 0.2%, 0.3%) of AgNPs on the properties of the composite films were investigated, and its appearance, mechanical properties, microstructure and antibacterial properties were characterized, in order to provide theoretical support for the development of preservation materials for storing Ougan. The results showed that as the content of AgNPs increased, the inhibitory effect of the composite film on the growth of Penicillium citrinum became more significant (P<0.05). Among them, the composite film with 0.1% AgNPs content had the best comprehensive performance, its tensile strength reached 12.45 MPa, elongation at break was 6.47%, water vapor permeability was 21.03×10−6 g·mm/(m2·s·Pa), and oxygen permeability was 2.31×10−6 cm3/(cm2·s·Pa). Scanning electron microscopy (SEM) showed that composite film with 0.1% AgNPs content was regular, compact and evenly distributed in cross section. Infrared spectroscopy and thermogravimetric analysis showed that composite film with 0.1% AgNPs content had good bonding and thermal stability. 0.1%AgNPs@PVA/MC composite film could effectively reduce the weight loss rate of Ougan during storage, and reduce the consumption rate of soluble solid, titratable acid and VC, delay the maturation of Ougan and significantly inhibit the growth of Penicillium citrinum, which could better maintain the quality of Ougan during the storage period, this study provided support for the sustainable development of Ougan industry.